Fundamentals of Ecology - Odum, Eugene P. (Cengage Learning, 2005)
Master the study of ecology in the twenty-first century with FUNDAMENTALS OF ECOLOGY! Designed to educate a wide audience about ecological science, this biology text shows you the application of ecological principles in the real world and how to use what you learn to solve problems in fields such as resource management, conservation biology, ecological toxicology, ecosystem health, landscape ecology, and restoration ecology. Introductory statements, diagrams, models, photographs, and a book-specific website are just a few of the tools found throughout the text that will help you succeed.